The last reconnection of the Marmara Sea (Turkey) to the World Ocean: A paleoceanographic and paleoclimatic perspective - McHugh, C. M. G.; Gurung, D.; Giosan, L.; Ryan, W. B. F.; Mart, Y.; Sancar, U.; Burckle, L.; Cagatay, M. N. (Marine Geology, 2008)
During the late glacial, marine isotope Stage 2, the Marmara Sea transformed into a brackish lake as global sea-level fell below the sill in the Dardanelles Strait. A record of the basin's reconnection to the global ocean is preserved in its sediments permitting the extraction of the paleoceanographic and paleoclimatic history of the region. The goal of this study is to develop a high-resolution record of the lacustrine to marine transition of Marmara Sea in order to reconstruct regional and global climatic events at a millennia] scale. For this purpose, we mapped the paleoshorelines of Marmara Sea along the northern, eastern, and southern shelves at Cekmece. Prince Islands, and Imrali, using data from multibeam bathymetry, high-resolution subbottom profiling (chirp) and ten sediment cores. Detailed sedimentologic, biostratigraphic (foraminifers, mollusk, diatoms), X-ray fluorescence geochemical scanning, and oxygen and carbon stable isotope analyses correlated to a calibrated radiocarbon chronology provided evidence for cold and city conditions prior to 15 ka BP, warm conditions of the Bolling-Allerod from similar to 15 to 13 ka BP, a rapid marine incursion at 12 ka BP, still stand of Marmara Sea and sediment reworking of the paleoshorelines during the Younger Dryas at similar to 11.5 to 10.5 ka BP, and development of strong stratification and influx of nutrients as Black Sea waters spilled into Marmara Sea at 9.2 ka BR Stable environmental conditions developed in Marmara Sea after 6.0 ka BP as sea-level reached its present shoreline and the basin floors filled with sediments achieving their present configuration. (C) 2008 Elsevier B.V. All rights reserved.
id: 801; 370ED Times Cited:4 Cited References Count:104; YY